Poly herbal extraction for analgesic and anti-inflammatory activity - Chitta, Venkateswararao; Venkataramana, K.; Rajesham, V.V.; Nagaurjunareddy, G. (International Journal of Pharmacology and Toxicology, 2014)
The analgesic and anti-inflammatory activity of the poly herbal formulation (composed of the extracts from Terminalia chebula, tinospora cordifolia, Phyllanthus emblica, Portulaca oleracea) was evaluated in Acetic Acid Induced Writhing Method, Eddy’s Hot Plate Method: (Thermal stimulus), Carrageenan induced hind paw edema. The extract at dose of 200, 400 mg/kg produced significant inhibition of oedema and pain induced by above mentioned methods. The result obtained suggesting that extract possesses significant analgesic and anti-inflammatory activity.   Keywords: Analgesic, Anti Inflammatory, Phyllanthus Emblica, Portulaca Oleracea, Terminalia Chebula, Tinospora Cordifolia.